Analisis Penerapan Enterprise Resource Planning (ERP) dalam Order Pembelian Bahan Baku di PT Varia Usaha Beton - Widayati, Nadyla Citra; Vendy, Vicky (YUME : Journal of Management, 2025)
The purpose of this study is to analyze the raw material purchase order procedure of PT Varia Usaha Beton, and to analyze the internal control in the raw material purchasing system at PT Varia Usaha Beton which is integrated with the Enterprise Resource Planning (ERP) system. This study was conducted with a qualitative approach through a case study method. Data collection techniques include observation, interviews with 3 informants and documentation. The research findings indicate that internal control in the raw material purchasing system at PT Varia Usaha Beton has not been running optimally as indicated by several weaknesses in its implementation, manual document creation, the length of the approval process between divisions which can take one to two days in each division, and the use of two software used for the raw material purchase order process, namely the Sunfish and VisWeb ERP systems which have not been fully integrated, the use of separate systems results in duplicate work, and the risk of data input errors. As a solution, the company needs to evaluate the running system and process automation to improve operational effectiveness. This study shows the importance of continuous evaluation of the company's information system. This research can be a basis for company management in making strategic decisions to minimize errors and support more accurate and efficient processes.Keywords: ERP; Purchase Order Procedure; Raw Materials; PT Varia Usaha Beton